Public space democracy
1 online resource.
Keywords: "This volume takes a global view of the emergence of public protest movements over the last decade, asking whether such movements contribute to the globalization of civil society. Through a variety of studies, organised around the themes of public agency, public norms, public memory and public art, it considers the tendency of political contestations to move beyond national boundaries and create transnational connections. Departing from the approaches of social movements perspectives, it focuses on public space as a site of social 'mixity' and opens up a new field for the study of politics and cultural controversies. An analysis of the paradigmatic change in the way in which society is made and politics is conducted, this study of the new enactment of citizenship in public space will appeal to scholars of sociology, anthropology, geography and politics with interests in protest movements and contentious politics, citizenship and the public sphere, and globalisation"--